ABOUT CRITERIA OF CHOICE OF OPTIMAL CHILL AUXILIARIES ON THE BASIS OF METHODS OF THE AUTOMATED MODELING SYSTEMS - A. N. Chichko; T. V. Matiushinets; L. V. Markov (Литьë и металлургия)
The structural outline of automation of the chill mold auxiliaries is worked out. The criteria of choice of optimal chill mold auxiliaries construction, based on numerical methods of modeling, are offered.